PERLINDUNGAN HUKUM TRADISI OKOKAN SEBAGAI EKSPRESI BUDAYA TRADISIONAL - Putri, Putu Dinanda Prajna; Pratiwi, Ida Ayu Windhari Kusuma (Universitas Tabanan, 2023)
This okokan is a necklace or keroncong made of wood which is usually hung around the cow's neck as a form of pride. The okokan, if shaken, will emit a loud and rumbling sound when played in a crowd. The Okokan tradition is a tradition in Bali and is one of the expressions of traditional culture. This research has the objective of identifying, analyzing and describing the regulations relating to the okakan tradition in the perspective of copyright according to the laws in force in Indonesia. This research uses a juridical-normative method, where this juridical-normative research method prioritizes research based on literature. The concept of cultural heritage in the form of material cultural heritage in the form of cultural heritage objects that have comfort with traditional cultural expressions in the realm of copyright. Legal protection for creations that are related to communal and traditional values such as traditional ceremonies, is given in forms of traditional cultural expression. This legal protection is regulated in Article 38 paragraph (1) of the Copyright Law. Legal protection of traditional cultural expressions is an opportunity for society in general to obtain ancestral legacies in the form of intellectual works. Legal protection arrangements regarding traditional cultural expressions are strictly regulated in the Copyright Law which stipulates that traditional cultural expressions are held by the state. Benefit sharing in terms of the use of traditional cultural expressions in the Law on the Advancement of Culture stipulates that the results of benefit sharing are distributed to revive and maintain objects of cultural promotion in the form of these traditional cultural expressions. Legal arrangements governing the legal protection of traditional cultural expressions are regulated in the Copyright Law which stipulates that the copyright to traditional cultural expressions is held by the State, but these legal arrangements are not sufficient in terms of legal protection of traditional cultural expressions, because the Copyright Law contains blurring of norms regarding the use or utilization of economic rights of traditional cultural expressions.